Pengaruh Harga, Kemudahan Transaksi dan Kepercayaan Terhadap Keputusan Pembelian di Toko Online Tiktok Shop: Studi Kasus pada Mahasiswa Universitas Methodist Indonesia Fakultas Ekonomi Program Studi Manajemen Angkatan 2021 (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine and analyze the effect of price, ease of transaction and trust on purchasing decisions at the TikTok shop online store. The type of research used is quantitative data. The sample in this study was 76 people. Based on the results of the t hypothesis test, it can be concluded that price partially has a positive and significant effect on purchasing decisions, ease of transaction partially does not affect purchasing decisions, trust partially has a positive and significant effect on purchasing decisions. Based on the results of the F hypothesis test, it can be concluded that price, ease of transaction and trust simultaneously have a positive and significant effect on purchasing decisions.